Effects of combined extracts of Lepidium meyenii and Allium tuberosum Rottl. on erectile dysfunction - Yi Zhang; Feixian Zhou; Fahuan Ge (BMC, 2019)
Abstract Background Sexual problems are widespread and adversely affect the interpersonal relationships and the quality of life. Currently, synthetic drugs improving sexual function are available, but expenditures for such agents are extremely high. To discover relatively inexpensive, widely available and effective natural drugs, we identified a combined extracts from Lepidium meyenii (maca) root and Allium tuberosum Rottl. (Chinese chive) seed, assessed the effects of this combined extracts on erectile dysfunction, and explored its potential mechanisms. Methods The extracts were obtained via supercritical fluid extraction. Male BALB/c mice received doses of extract from single plant or the combined extracts (200 mg/kg) by gastric gavage for 14 d, and Viagra was used as the positive control drug. Sexual behaviour was observed, and concentrations of serum testosterone, nitric oxide (NO), and cyclic guanosine monophosphate (cGMP) in serum as well as in penis were measured. In addition, weights of genital organs were also measured. Results The combined extracts of maca root and Chinese chive seed (1:1, w/w) had a 45-fold increase in macamide content compared with maca extract. It also led to significantly higher ejaculation frequency (P < 0.05) than single extract from maca root or Chinese chive seed, with no corresponding effect on genital indices. In addition, the NO level in serum (P < 0.01) and penis (P < 0.05) increased notably, as well as the level of cGMP in penis (P < 0.05). Conclusions The results indicated that the combined extracts produced better synergistic effects on male sexual function than maca extract or Chinese chive extract alone. These positive effects may involve the upregulation of NO and cGMP concentrations in penis.